The Use of Quizizz Media to Improve Elementary Students’ Understanding of the Simple Future Tense and Future Continuous Tense - Citra Novita Purba; Khalisa Nazla; Nazwa Pasha; Irene Angelina Pandiangan; Nanda Ramadani (MUDABBIR Journal Research and Education Studies, 2025)
Elementary school students' understanding of English tenses, especially Simple Future Tense and Future Continuous Tense, is still considered low. This is due to the limited variety of learning media applied in the classroom and the learning methods that tend to be traditional. Therefore, this study aims to improve elementary school students' understanding of the two forms of tenses by utilizing Quizizz media, an interactive and fun digital quiz learning platform. The research method applied is Classroom Action Research (CAR) which is carried out in two cycles. The research subjects consisted of 30 sixth grade students at a public elementary school in 064037 Medan Tembung. Data collection methods include pre-test and post-test, observation of student learning activities, and student response questionnaires regarding media utilization. Data analysis was carried out quantitatively and qualitatively to observe improvements in learning outcomes and student responses. The study showed a significant increase in student understanding after using Quizizz media. The average student score increased from 62.5 in the pre-action to 74.8 in cycle I, and reached 83.2 in cycle II. In addition, the majority of students showed increased active involvement in the learning process and positive reactions to the use of Quizizz. From the results of the study, it can be concluded that the use of Quizizz media is effective in improving elementary school students' understanding of Simple Future Tense and Future Continuous Tense, and is able to create a more interesting and meaningful learning atmosphere.